THE UNEXPECTED LEADER : Exploring the real nature of values, authenticity and moral purpose in education - Small, Iesha (Independent Thinking Press, 2019)
Iesha Small's 'The Unexpected Leader: Exploring the real nature of values, authenticity and moral purpose in education' is for school leaders who want to make a difference but feel they aren't obvious leadership material. This is a book about people. A book that humanises school leaders and tells their stories. A book in which school leaders reveal their authentic selves and their journeys to leadership.